Penaksiran Risiko Bencana Gempa Bumi Di Kecamatan Bonto Bahari Kabupaten Bulukumba - Harry Hardian Sakti; Andi Idham Asman; Despry Nur Annisa Ahmad; Muhammad Fakhruddin; Muhammad Isra (Institut Teknologi Sepuluh Nopember, 2022)
The location of Bonto Bahari district on the fault of Walanae implicates a potential earthquake disaster. Bonto Bahari District on the spatial plan of Bulukumba in the year of 2012-2032 is set as a Regency Special Economic Zones (SEZs) for Marine tourism. Justifying the stipulation of the rules, it should be integrated into geological risk in order for sustainable development of tourist activities in the Bonto Bahari District. The purpose of this study are: (1) analyzing the hazard of an earthquake in Bonto Bahari district; (2) analyzing the vulnerability of earthquakes in Bonto Bahari district; and (3) analyzing the risk of earthquakes in Bonto Bahari district. The methods used are quantitative-qualitative and spatial analysis. Research shows maps of the hazard levels of earthquakes, maps of earthquake vulnerabilities, and maps of earthquake risk levels. The research is expected to provide input to local governments on taking early preparedness measures in response to the threat of an earthquake disaster in the Bonto Bahari district.